The Wanderings of Gut-Derived IgA Plasma Cells: Impact on Systemic Immune Responses - Keppler, Selina J.; Goess, Marie Christine; Heinze, Julia M. (Frontiers in Immunology, 2021)
Humoral immunity is mainly mediated by a B cell population highly specialized to synthesize and secrete large quantities of antibodies – the antibody-secreting cells (ASC). In the gastrointestinal environment, a mixture of foreign antigens from the diet, commensal microbiota as well as occasional harmful pathogens lead to a constant differentiation of B cells into ASC. Due to this permanent immune response, more than 80% of mammalian ASC reside in the gut, of which most express immunoglobulin A (IgA). IgA antibodies contribute to intestinal homeostasis and can mediate protective immunity. Recent evidence points at a role for gut-derived ASC in modulating immune responses also outside of mucosal tissues. We here summarize recent evidence for wandering ASC, their antibodies and their involvement in systemic immune responses.